2015
DOI: 10.2147/dhps.s83770
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of antibiotic prescription errors in an emergency department, Central Saudi Arabia

Abstract: BackgroundInappropriate antibiotic (ATB) prescriptions are a threat to patients, leading to adverse drug reactions, bacterial resistance, and subsequently, elevated hospital costs. Our aim was to evaluate ATB prescriptions in an emergency department of a tertiary care facility.MethodsA cross-sectional study was conducted by reviewing charts of patients complaining of infections. Patient characteristics (age, sex, weight, allergy, infection type) and prescription characteristics (class, dose, frequency, duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…The economic and public health burdens of UTIs is substantial and markedly affect the quality of life of infected patients [ 6 ]. In Saudi Arabia, UTIs were reported to be the second leading cause of infections predominately in women at ED [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The economic and public health burdens of UTIs is substantial and markedly affect the quality of life of infected patients [ 6 ]. In Saudi Arabia, UTIs were reported to be the second leading cause of infections predominately in women at ED [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, regarding the aforementioned aspect, one study revealed that 23% of antibiotic prescriptions in the United States are inaccurate [7]. In Saudi Arabia, > 46% of prescriptions are written for clinical conditions for which antibiotics are not indicated [8], and in Colombia, a study revealed that between 29.2 and 67.4% of the doctors surveyed have incorrect knowledge regarding antibiotic prescription [9].…”
Section: Introductionmentioning
confidence: 99%
“…The present study found 19% prevalence of antibiotic by self-prescription which was higher than that found by Mossa et al 11 in Ethiopia and Widayati et al 12 in Indonesia who reported a prevalence of 6.7% and 7.3% respectively. Whereas, it was less than a prevalence reported by other studies conducted in Sudan 13 , UAE 14 , Egypt 15 , and other region in Saudi Arabia [4][5][6][7][8][9] . These differences can be explained by different characteristics of populations and health systems.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, the majority of studies about antibiotics misuse have been conducted in the countries of Middle East, African and Central Asian countries. [4][5][6][7][8][9] In Saudi Arabia, recently patients visited community pharmacies to obtain the antibiotics without medical prescription. In 2013, a cross sectional study in pharmacists was conducted to assess their responses to selfmedication.…”
Section: Introductionmentioning
confidence: 99%